2012
DOI: 10.1016/j.micinf.2011.10.006
|View full text |Cite
|
Sign up to set email alerts
|

The role of interleukin-15 in inflammation and immune responses to infection: implications for its therapeutic use

Abstract: Interleukin-15 (IL-15) is a pleiotropic cytokine with a broad range of biological functions in many diverse cell types. It plays a major role in the development of inflammatory and protective immune responses to microbial invaders and parasites by modulating immune cells of both the innate and adaptive immune systems. This review provides an overview of the mechanisms by which IL-15 modulates the host response to infectious agents and its utility as a cytokine adjuvant in vaccines against infectious pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
122
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(129 citation statements)
references
References 136 publications
(192 reference statements)
6
122
0
1
Order By: Relevance
“…IL-15 is known to cause considerable toxicity in nonhuman primates at higher doses. Adverse side effects included weight loss and skin rash (37)(38)(39). Most recently, Conlon et al (19) reported hypotension, thrombocytopenia, liver injury, fever, and rigors in cancer patients receiving IL-15.…”
Section: Discussionmentioning
confidence: 99%
“…IL-15 is known to cause considerable toxicity in nonhuman primates at higher doses. Adverse side effects included weight loss and skin rash (37)(38)(39). Most recently, Conlon et al (19) reported hypotension, thrombocytopenia, liver injury, fever, and rigors in cancer patients receiving IL-15.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, IL-15 is now recognized as a cytokine with potent survival and immunomodulatory effects on cells of both the innate and the adaptive immune systems, including activating and expanding NK cells, NKT cells, CD8 þ effector memory, and central memory T lymphocytes, which play a central role in defense mechanisms against pathogens, and it is elevated in preterm labor. 39,40 It has also been demonstrated that IL-17A is involved in the development of inflammation by inducing the expression of proinflammatory cytokines, chemokines, antimicrobial peptides, and matrix metalloproteinases from different cells, and it is also the signature cytokine of the recently identified Th17 cell subset. 41 A recent study showed that Th17 cell number is increased in the chorioamniotic membrane of preterm delivery cases with choroamnionitis (CAM) and IL-17 levels in severe CAM preterm delivery cases were significantly higher than those in CAM-negative preterm delivery cases.…”
Section: Discussionmentioning
confidence: 99%
“…The synergistic interaction of cytokine and TCR signal has also been reported in the context of IL-15. IL-15 is a pleiotropic cytokine often produced early during infection by a wide range of cells with potent survival and immunomodulatory effects on T-cells[53]. IL-15 expression within inflamed tissues can provide a co-stimulatory signal to drive memory T-cell effector function[54].…”
Section: Mait Cell Activation Requirements and Implications For Thmentioning
confidence: 99%